Design and development of caffeic acid conjugated with Bombyx mori derived peptide biomaterials for anti-aging skin care applications. Issue 48 (12th June 2017) - Lee, Hoomin; Vilian, A. T. Ezhil; Kim, Jun Yeong; Chun, Myeung Hwan; Suh, Jung Sang; Seo, Hyo Hyun; Cho, Seung Hee; Shin, Il Soo; Kim, Sung Jun; Park, Seok Hoon; Han, Young-Kyu; Lee, Jeong Hun; et al.
Abstract : This study examined the significant features of caffeic acid conjugated with peptide (APPPKK) to determine if it meets the requirements for a cosmetic anti-aging biomolecule. Abstract : Over the last few centuries, aging-related diseases have become a part of the global health care problem. The skin is essentially more sensitive to aging because it is influenced by environmental exposure and genetic (genetically determined) processes. The use of a suitable cosmetic anti-aging material using a biomolecule with conventionally important medicine can help to protect damaged skin tissue. A new topical cosmetic anti-aging material should simulate the function of an extracellular matrix with its enhanced physiochemical, biological oxidative stress, and antioxidant properties. This study examined the significant features of CA–APPPKK (caffeic acid conjugated with peptide (APPPKK)) to determine if it meets the requirements for a cosmetic anti-aging biomolecule. Non-toxic CA–APPPKK was synthesized using a simple approach and CA stabilized with a peptide to form the new biomaterials. The cytotoxicity of the CA–APPPKK was examined with a CCK-8 assay and a reactive oxygen species (ROS) assay to evaluate the biological applications. CA–APPPKK caused a decrease in cell viability and membrane damage, and the degree of induction was dose dependent. The longevity-extending role of CA–APPPKK was attributed to its anti-oxidative activity and increased oxidative stress resistance. The anti-inflammatory capacity of CA–APPPKK was measured using a NO assay. This new approach indicates that CA–APPPKK is a potentially cosmetic anti-aging biomaterial for the prevention of oxidative stress-induced premature skin ageing and can be used to study aging-related diseases.